Identification of Signaling Pathways Targeted by the Food Contaminant FB1: Transcriptome and Kinome Analysis of Samples from Pig Liver and Intestine. Issue 12 (17th October 2017) - Régnier, Marion; Gourbeyre, Pascal; Pinton, Philippe; Napper, Scott; Laffite, Joëlle; Cossalter, Anne‐Marie; Bailly, Jean‐Denis; Lippi, Yannick; Bertrand‐Michel, Justine; Bracarense, Ana Paula F.R.L.; Guillou, Hervé; Loiseau, Nicolas; et al.
Abstract : Scope: Fumonisin B1 (FB1) is a mycotoxin produced by Fusarium species. In mammals, this toxin causes widespread organ‐specific damage; it promotes hepatotoxicity, is immunotoxic, alters intestinal functions etc. Despite its inhibitory effect on de novo ceramide synthesis, its molecular mechanism of action and toxicity is not totally elucidated. Methods and results: To explore the mechanism of FB1 toxicity, we analyzed the transcriptome and the kinome of two organs targeted by FB1: the liver and the jejunum. Pigs were fed for 4 weeks a control diet or a FB1‐contaminated diet (10 mg/kg). As expected, FB1‐exposed pigs gained less weight and displayed a higher sphinganine/sphingosine ratio. Comparison of the transcriptomes and the kinomes of treated versus control pigs showed striking differences. Among the disrupted pathways in liver and jejunum, we highlight Protein Kinase B (AKT) / Phosphatase and tensin homolog (PTEN) at the intersection of the FB1‐modulated pathways. Conclusion: Most of the effects of FB1 are mediated by the regulation of ceramide level, which influences protein phosphatase 2 (PP2A) and the phosphoinositide 3‐kinase (PI3K)/AKT signaling pathway. This pathway might be a new target to counteract toxic effect of Fumonisin B1, which is one of the most spread food contaminant in the world. Abstract : FB1 is one of the most spread mycotoxin in the world which induces a broad spectrum of damage in mammals. The molecular mechanism of action of this toxin remaining unclear, a comparative approach with transcriptome and kinome profiles is used to highlight PP2A and PI3K/AKT as key signaling pathways involved in FB1 toxicity. It is assumed that this key point might be a good target to develop a new antimycotoxin strategy in the future.